Sosialisasi dan Pelatihan Pembuatan Filtrasi Air Bersih di Kampung Hobong Distrik Sentani, Jayapura - Bambang Suhartawan; Suyatno Suyatno; Sapari Sapari; Helen Riupassa (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Access to clean water is still a crucial problem in Hobong Village, Sentani District, Jayapura, which has an impact on the high number of water-related diseases. Initial observations show that 78% of people in this area still use Lake Sentani water without adequate treatment, even though studies show that the quality of the lake water has decreased due to pollution. This community service program aims to improve community knowledge and skills in clean water treatment through a simple filtration system. The methods used include community education in the form of socialization of the importance of clean water, diffusion of science and technology through the creation of filtration system prototypes, training in filter creation and maintenance, mediation between stakeholders, and advocacy for clean water policies. The results of the program showed an increase in community knowledge of up to 100%, with the highest increase in the aspect of filtration system maintenance (182.1%). The filtration system developed effectively reduced E. coli (97.9%), Total Coliform (93.3%), turbidity (84.4%), and color (82.9%). This program also succeeded in forming a Clean Water Care Community Group, encouraging the ratification of Village Regulations on Clean Water Management, and obtaining village fund allocations for the development of filtration systems. A 61.7% reduction in diarrhea cases in the 3-month post-program period proves that a comprehensive approach to providing clean water can have a significant impact on public health in remote areas.